Multimodality in the front covers of chick-lit books / Melissa Khoo Yen Li - Melissa Khoo , Yen Li (2019)
This research aimed to study how chick-lit book covers utilise the complementary relationship between text and visual elements to provide more effective ways of meaning making. This use of multiple forms of modes, or better known as „multimodality‟, was studied in terms of its features, as well as how these features represent the chick-lit genre. From a social semiotic perspective, this study analysed the data in the form of twelve chick-lit book covers by looking at three main elements: the text, composition and representation of the social actors found on the covers. The goal was to determine if patterns could be found in the use of certain multimodal features and how these deployments of modes, as a whole, represent the chick-lit genre. In addition, this study also looked into how gender is represented on the book covers of this genre, given that chick-lit is a genre written by women, about women and for women.